Emotional Experience, Destination Image, Tourist Satisfaction Sebagai Antaseden Revisit Intention Wisatawan Curug Cileat Subang - Salsabila, Rasikah Agustin; Ernawadi, Yadi (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study aims to examine the effect of emotional experience and destination image on revisit intention mediated by tourist satisfaction of Curug Cileat Subang tourists. 120 tourists who experienced visiting Curug Cileat Subang were involved as respondents. The cross sectional or one shot method was used to obtain data. This instrument has passed validity and reliability tests which include convergent validity, discriminant validity and composite reliability.The data analysis technique used is structural equation modeling (SEM) using SmartPLS version 3.0. From the thirteen hypotheses proposed, eight were supported by empirical data. With the results of this study emotional experience, cognitive image, affective image and unique image have a direct effect on revisit intention and affective image has an indirect effect on revisit intention through tourist satisfaction. Based on the results of this study, it is hoped that it can provide benefits for further researchers and the management of the object being assessed or a similar tourist industry related to designing strategies relevant to improving the quality of these attributes.